1995
DOI: 10.1007/bf00008180
|View full text |Cite
|
Sign up to set email alerts
|

Metal content of some green and brown seaweeds from Antikyra Gulf (Greece)

Abstract: An analysis was made of the levels of Fe, Cu, Zn, Cd, Pb, Na, K, Ca and Mg in three green and four brown seaweeds, abundant in the Antikyra Gulf (Viotia, Greece). After Ca and the macroelements K, Mg, Na, the higher concentrations found were of Fe and Pb, with Fe>Pb. Cadmium content was low in most species. Differences between species and taxonomic groups were also considered. Fe, Zn, Cd and Ca in the green alga Dasycladus vermicularis increased from March to July and had their maxima in summer or autumn (Cd),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Higher levels of adhered particles could therefore lead to greater abundances of Re and Os in macroalgae. Moreover, it has previously been suggested that the selectivity coefficient between macroalgae polyphenolic proteins and metals such as Cu, Zn, Cd, As, Pb, Ag, and Cr exceeds the binding strength of these metals with sediment particles, allowing macroalgae to scavenge these metals directly from particulates (Barreiro et al, ; Haritonidis & Malea, ; Luoma et al, ; Malea et al, ; Ragan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of adhered particles could therefore lead to greater abundances of Re and Os in macroalgae. Moreover, it has previously been suggested that the selectivity coefficient between macroalgae polyphenolic proteins and metals such as Cu, Zn, Cd, As, Pb, Ag, and Cr exceeds the binding strength of these metals with sediment particles, allowing macroalgae to scavenge these metals directly from particulates (Barreiro et al, ; Haritonidis & Malea, ; Luoma et al, ; Malea et al, ; Ragan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of accumulation can be influenced by growth rate, the age of the alga and abiotic factors, such as temperature, nutrient availability, light intensity and salinity (Malea et al . ; Mamboya et al . ).…”
Section: Nutritional Components Of Macroalgae For Aquafeedsmentioning
confidence: 99%
“…Furthermore, examination of the correlation matrix between variables (Figure 4), revealed the presence in the corallina of a positive significant correlation between Cd and Pb which may have a common source which is sediment or seawater, on the other hand, a negative correlation between Zn and Pb in this alga, may indicate that they are competing for the binding sites of the alga [15], or they are transported in these stations from different sources and follow a pattern of distribution [16]. On the other hand, the trend of BSAF in Corallina officinalis was in the ordre: Cd > Pb > Ni > Cu > Zn > Fe.…”
Section: Resultsmentioning
confidence: 99%